PENGARUH SISTEM PENGGAJIAN, PEMBERDAYAAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KECAMATAN SITOLU ORI KABUPATEN NIAS UTARA - HAMONANGAN SIALLANGAN (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The purpose of this study is to investigate, analyze and obtain empirical evidence about the influence of the reward system, empowerment and motivation on employee performance at the District Office of Sitolu Ori North Nias. Â The data used are secondary data which obtained by distributing questionnaires to the respondents. SPSS was used to analyze the research purpose .Findings revealed that all three hypotheses were tested acceptable . The result of estimation revealed that there is a positive and significant relationship between the reward system, empowerment, and motivation on performance at District Office of Sitolu Ulu North Nias staff.